Metabolic engineering of the fungal D-galacturonate pathway for L-ascorbic acid production. Issue 1 (December 2015) - Kuivanen, Joosu; Penttilä, Merja; Richard, Peter
Abstract Background Synthetic L-ascorbic acid (vitamin C) is widely used as a preservative and nutrient in food and pharmaceutical industries. In the current production method, D-glucose is converted to L-ascorbic acid via several biochemical and chemical steps. The main source of L-ascorbic acid in human nutrition is plants. Several alternative metabolic pathways for L-ascorbic acid biosynthesis are known in plants. In one of them, D-galacturonic acid is the precursor. D-Galacturonic acid is also the main monomer in pectin, a plant cell wall polysaccharide. Pectin is abundant in biomass and is readily available from several waste streams from fruit and sugar processing industries. Results In the present work, we engineered the filamentous fungusAspergillus niger for the conversion of D-galacturonic acid to L-ascorbic acid. In the generated pathway, the native D-galacturonate reductase activity was utilized while the gene coding for the second enzyme in the fungal D-galacturonic acid pathway, an L-galactonate consuming dehydratase, was deleted. Two heterologous genes coding for enzymes from the plant L-ascorbic acid pathway – L-galactono-1, 4-lactone lactonase fromEuglena gracilis (EgALase ) and L-galactono-1, 4-lactone dehydrogenase fromMalpighia glabra (MgGALDH ) – were introduced into theA. niger strain. Alternatively, an unspecific L-gulono-1, 4-lactone lactonase (smp30 ) from the animal L-ascorbic acid pathway was introduced in the fungal strain instead of the plant L-galactono-1, 4-lactone lactonase. In addition, a strain with the production pathway inducible with D-galacturonic acid was generated by using a bidirectional and D-galacturonic acid inducible promoter from the fungus. Even though, the lactonase enzyme activity was not observed in the resulting strains, they were capable of producing L-ascorbic acid from pure D-galacturonic acid or pectin-rich biomass in a consolidated bioprocess. Product titers up to 170 mg/l were achieved. Conclusions In the current study, an L-ascorbic acid pathway using D-galacturonic acid as a precursor was introduced to a microorganism for the first time. This is also the first report on an engineered filamentous fungus for L-ascorbic acid production and a proof-of-concept of consolidated bioprocess for the production.